Changes onÂ soil structural stability afterÂ in natura andÂ composted chicken manure application - Thadeu Rodrigues De Melo; Alex Figueiredo; Wesley Machado; JoÃ£o Tavares Filho (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Many studies evaluate the effect of successive applications of chicken manure on soil attributes. In Brazil, the commercialization of this waste is common, implying on its sporadic use instead of many applications at the same area. The short-term effects of a single application of chicken manure and the role of its composting on soil structural stability are not fully understood. This study investigated application of in natura (uncomposted) and composted chicken manure on the structural stability of a Rhodic Ferralsol after a short period following single application. Methods The experiment was performed in a Rhodic Ferralsol in Londrina, ParanÃ¡. Brazil. We applied in natura and composted chicken manure at doses of 4.5, 9.0, 13.5, and 18.0 Mg haâ1 plus a control without application. Soil samples were collected after 185 days at the 0.0â20.0 cm layer for laboratorial analysis. Results The composting of chicken manure did not afect soil structural stability. Chicken manure did not alter water-dispersible clay (xÌ = 21.7%), but increased the mean weight diameter of water-stable aggregates (MWD=5.43+0.068Ãdose) through the agglomeration of aggregates with 0.5â4 mm into 8â19 mm. Conclusion Even after a short period of 185 days, the application of chicken manure increases the structural stability of Rhodic Ferralsols and its composting, in the way performed by many farmers, is not associated with the improvement of soil structural stability in short-term. However, other advantages arise from the composting of the manure and need to be considered prior its use.